Friction Stir Welding and Processing IX - Hovanski, Yuri; Mishra, Rajiv; Sato, Yutaka; Upadhyay, Piyush; Yan, David (Springer International Publishing : Imprint: Springer, 2017)
This books presents a current look at friction stir welding technology from application to characterization and from modeling to R&D. It is a compilation of the recent progress relating to friction stir technologies including derivative technologies, high-temperature applications, industrial applications, dissimilar alloy/materials, lightweight alloys, simulation, and characterization. With contributions from leaders and experts in industry and academia, this will be a comprehensive source for the field of Friction Stir Welding and Processing.
Keywords: Materials science.; Engineering -- Materials.; Metals.; elektronické knihy; electronic books